Comparison of Left Atrial and Biatrial Maze Procedure in the Treatment of Atrial Fibrillation: A Meta-Analysis of Clinical Studies - Zheng, Shuai; Zhang, Haibo; Li, Yan; Han, Jie; Jia, Yixin; Meng, Xu (The Thoracic and Cardiovascular Surgeon, 2016)
Background The outcomes of atrial fibrillation (AF) between biatrial maze (BAM) and left atrial maze (LAM) are still controversial. The purpose of this study was to compare the clinical and rhythm outcomes between BAM and LAM in patients with AF.Methods Electronic databases and article references were systematically searched (1990–2014) to access relevant studies. Odds ratio (OR) and weight mean difference (WMD) with 95% confidence interval (CI) were reported.Results Fourteen studies with 2,075 patients were finally involved in the present meta-analysis. The rate of restored sinus rhythm (SR) was similar in BAM and LAM groups (OR: 1.25, 95% CI: 0.91–1.72, p = 0.163). BAM reduced the prevalence of atrial flutter during follow-up (OR: 0.12, 95% CI: 0.01–0.96, p = 0.046). Compared with BAM, LAM shorten aortic cross-clamping time (WMD = 9.05 minutes, 95% CI: 1.28–16.82, p = 0.023) and cardiopulmonary bypass time (WMD = 20.21 minutes, 95% CI: 7.40–33.03, p = 0.002). No significant difference was found between groups in the risk of death (OR: 1.22, 95% CI: 0.70–2.14, p = 0.233), cerebrovascular events (OR: 1.44, 95% CI: 0.51–4.06, p = 0.493), and reoperation for bleeding (OR: 1.34, 95% CI: 0.70–2.55, p = 0.374). However, the risk for implantation of permanent pacemaker was significantly higher in BAM group (OR: 2.60, 95% CI: 1.09–6.20, p = 0.031).Conclusion No significant difference was found between BAM and LAM in the rate of restored SR, the risk of death, cerebrovascular events, and reoperation for bleeding. BAM is superior to LAM in reducing the prevalence of atrial flutter during follow-up, but LAM shortens the aortic cross-clamping time and cardiopulmonary bypass time, and decreases the risk of permanent pacemaker implantation.
Keywords: meta-analysis; atrial fibrillation; maze procedure